Palm kernel fatty acid distillate as substrate for rhamnolipids production using Pseudomonas sp. LM19 - Thio, Cui Wen; Lim, Wen Huei; Md. Shah, Umi Kalsom; Phang, Lai Yee (Taylor & Francis, 2022)
Biosurfactants have been used in various industries due to their high surface activity, high biodegradability and low toxicity. However, the applications of biosurfactants are still limited due to their production and cost. This work aimed to determine the viability of palm kernel fatty acid distillate (PKFAD) as an alternative substrate for biosurfactant production using locally isolated Pseudomonas sp. LM19. Optimum conditions for biosurfactant production and characteristics of produced biosurfactants were studied. The results showed a 3.2-fold increase in biosurfactant concentration under optimum conditions: 2% (v/v) of PKFAD, pH 7.5, 170 rpm and 192 h incubation time, producing 1.6 g/L of biosurfactant. The produced biosurfactant was capable of reducing the surface tension to 27.7 mN/m with a critical micelle concentration (CMC) of 28 mg/L. Thin-layer chromatography showed presence of both lipid and sugar moieties, thus indicating the produced biosurfactant was glycolipid. Gas chromatography-mass spectrometry recorded the presence of rhamnolipid precursors, thereby revealing that the glycolipid produced was rhamnolipid. High-performance liquid chromatography determined the rhamnolipids produced was a combination of mono-rhamnolipids and di-rhamnolipids. The lipid moiety of both rhamnolipids produced boasted C10-C10 lipid chain majority. To conclude, PKFAD could be a potential substrate for biosurfactant production and add value to the industry.